NiSx / MoS2 composite material, preparation method and application thereof

By preparing NiSx/MoS2 composite materials, the self-assembly and vulcanization reaction of nickel-molybdenum precursor nanosheets are used to enrich heterogeneous interfaces and sulfur vacancy, and the lack of performance of pure MoS2 materials in the field of electromagnetic wave absorption is solved, and efficient electromagnetic wave absorption is achieved Effect.

CN119160956APending Publication Date: 2024-12-20ANHUI UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411350831.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing pure MoS2 materials have weak conductivity and limited polarization sites, resulting in poor electromagnetic absorption performance and poor polarization effect in the field of electromagnetic wave absorption.

Method used

By preparing NiSx/MoS2 composite materials, the nickel-molybdenum precursor nanosheets are synthesized using molybdenum source and nickel source to form 3D nanoflower spheres, and nanoflower spherical NiSx/MoS2 composite materials are prepared through vulcanization reaction, enriching heterogeneous interfaces and Sulfur vacancies improve polarization loss capability and impedance matching.

Benefits of technology

It significantly improves the polarization loss capability and electromagnetic wave absorption efficiency of NiSx/MoS2 composite materials, and meets the requirements of strong absorption, broadband, lightweight and thin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160956A_ABST
    Figure CN119160956A_ABST
Patent Text Reader

Abstract

The invention provides a NiS < x > / MoS2 composite material, a preparation method and application, and relates to the technical field of electromagnetic microwave materials, a Ni-Mo precursor nanosheet prepared from a molybdenum source and a nickel source is self-assembled to form 3D nano flower balls, the 3D nano flower balls and a sulfur source are subjected to a vulcanization reaction to prepare the NiS < x > / MoS2 composite material, and the NiS < x > / MoS2 composite material is a NiS / MoS2 composite material or a NiS / NiS < 2 > / MoS2 composite material; the preparation method comprises the following steps: S1, dissolving a molybdenum source, a nickel source and hexamethylenetetramine in water, and fully stirring to obtain a uniform solution; s2, the solution is subjected to a hydrothermal reaction, precipitates are taken out and subjected to washing and drying treatment, and a Ni-Mo precursor is prepared; and S3, the Ni-Mo precursor and a sulfur source are subjected to annealing treatment, and the NiS < x > / MoS2 composite material is prepared. In the vulcanization process, along with heterogeneous forming, violent movement of surface charges, a strong polarization effect caused by multiple heterogeneous interfaces, sulfur vacancies and other defects, the polarization loss capacity of the NiSx / MoS2 composite material is remarkably improved, the NiSx / MoS2 composite material is applied to the field of electromagnetic wave absorption, multiple reflection and scattering of electromagnetic waves are facilitated, and the electromagnetic wave absorption efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electromagnetic microwave materials, and in particular to a NiS x / MoS 2 Composite materials, preparation methods and applications thereof. Background Art

[0002] With the increasing popularity of electronic devices and the rapid development of electronic technology, the problem of electromagnetic pollution cannot be ignored. Especially with the promotion and application of 5G technology, electromagnetic radiation pollution poses an increasingly severe threat to national defense construction and people's livelihood security.

[0003] Therefore, it is urgent to research and develop advanced electromagnetic wave (EMW) absorbing materials to solve these problems and deal with the increasingly serious electromagnetic radiation pollution. Traditional electromagnetic wave (EMW) absorbing materials, such as ferrites and magnetic metals, are difficult to meet the requirements of strong absorption, broadband, light weight and thinness; while dielectric electromagnetic wave absorbing materials are difficult to meet actual needs due to their single loss mechanism, poor impedance matching, insufficient absorption intensity and insufficient effective absorption frequency band.

[0004] In recent years, transition metal disulfides (TMDs) have been widely studied due to their excellent performance in catalysis, energy storage and sensing. As a member of the TMDs family, MoS 2 It has excellent optical, electrical and mechanical properties. However, due to the 2 The material has relatively weak conductivity, limited polarization sites and poor stability. Its application in the field of electromagnetic wave (EMW) absorption will lead to problems such as poor electromagnetic absorption performance and poor polarization effect. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the shortcomings of the prior art, the present invention provides a NiS x / MoS 2 Composite materials, preparation methods and applications thereof solve the existing pure MoS 2 The material has relatively weak conductivity, limited polarization sites and poor stability, and its application in the field of electromagnetic wave (EMW) absorption will lead to technical problems such as poor electromagnetic absorption performance and poor polarization effect.

[0007] (II) Technical solution

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] NiS x / MoS 2The composite material is prepared by self-assembly of nickel-molybdenum precursor nanosheets prepared from molybdenum source and nickel source to form 3D nano flower balls, and the 3D nano flower balls are prepared by sulfurization reaction with a sulfur source; wherein NiS x NiS or NiS 2 , the NiS x / MoS 2 The composite material is NiS / MoS 2 Composite material or NiS / NiS 2 / MoS 2 Composite materials.

[0010] NiS x / MoS 2 The preparation method of the composite material specifically comprises the following steps:

[0011] S1. Dissolve the molybdenum source, nickel source and hexamethylenetetramine in water and stir thoroughly to obtain a uniform solution;

[0012] S2, the solution prepared in step S1 is subjected to a hydrothermal reaction, after the reaction is completed, it is cooled to room temperature, the precipitate is taken out, washed, and dried to obtain a Ni-Mo precursor;

[0013] S3, annealing the Ni-Mo precursor and the sulfur source under a specific atmosphere to obtain nano-flower-shaped NiS x / MoS 2 Composite materials.

[0014] The above NiS x / MoS 2 Composite material or NiS x / MoS 2 Preparation method of composite material NiS x / MoS 2 Composite materials are used in the field of electromagnetic microwave absorption.

[0015] (III) Beneficial effects

[0016] The present invention provides a NiS x / MoS 2 Composite material, preparation method and application thereof. Compared with the prior art, it has the following beneficial effects:

[0017] 1. First, the Ni-Mo precursor material is synthesized by hydrothermal method. During the synthesis of Ni-Mo precursor, two-dimensional nanosheets self-assemble to form 3D nanoflower balls. The interconnected nanosheets build a conductive network to provide a channel for the migration of electrons. Then, nanoflower-shaped NiS is prepared by high-temperature sulfurization method. x / MoS 2During the sulfurization process, accompanied by heterogeneous formation and drastic movement of surface charges, multiple heterogeneous interfaces and sulfur vacancies and other defects induce a strong polarization effect, which significantly improves the NiS x / MoS 2 Polarization loss capability of composite materials;

[0018] 2. NiS and MoS 2 Two-phase coexistence or NiS, NiS 2 and MoS 2 The coexistence of three phases, especially the coexistence of three phases, is conducive to enriching the heterogeneous interface and enhancing the interface polarization effect; and the three-dimensional nanoflower spherical structure optimizes the NiS x / MoS 2 The impedance matching of composite materials, when applied in the field of electromagnetic wave absorption, is beneficial to multiple reflections and scattering of electromagnetic waves, further improving the electromagnetic wave absorption efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 (a) is a SEM image of the Ni-Mo precursor prepared in Example 1 of the present invention, Figure 1 (b) is NiMoO prepared in Comparative Example 1 4 SEM images of Figure 1 (c) is NiS / MoS prepared in Example 1 of the present invention 2 SEM images of composite materials;

[0021] Figure 2 (a) is NiS / NiS prepared in Example 3 of the present invention 2 / MoS 2 TEM images of the composite materials. Figure 2 (b)-(d) are NiS / NiS prepared in Example 3 of the present invention. 2 / MoS 2 HRTEM images of the composite materials;

[0022] Figure 3 (a) is NiS / NiS prepared in Example 3 of the present invention 2 / MoS 2 Performance diagram of composite materials, Figure 3 (b) is NiMoO prepared in Comparative Example 2 of the present invention. 4Performance diagram of

[0023] Figure 4 (a)-(d) are NiS prepared in Examples 1-4 of the present invention respectively. x / MoS 2 Schematic comparison of minimum reflection loss diagrams of composite materials;

[0024] Figure 5 (a) is NiS prepared in Examples 1-4 of the present invention. x / MoS 2 The minimum reflection loss of the composite material corresponds to the three-dimensional diagram of the minimum reflection loss at different thicknesses. Figure 5 (b) is NiS / NiS prepared in Example 3 of the present invention 2 / MoS 2 The effective absorption bandwidth corresponding to the composite material. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The present application embodiment provides a NiS x / MoS 2 Composite materials, preparation methods and applications thereof solve the existing pure MoS 2 The material has relatively weak conductivity, limited polarization sites and poor stability, and its application in the field of electromagnetic wave (EMW) absorption will lead to technical problems such as poor electromagnetic absorption performance and poor polarization effect.

[0027] To solve the above technical problems, the overall idea of ​​the technical solution in the embodiment of the present invention is as follows:

[0028] The nanoflower spherical NiS provided in the embodiment of the present invention x / MoS 2 The composite material is first synthesized by hydrothermal method. In the synthesis of Ni-Mo precursor, two-dimensional nanosheets self-assemble to form 3D nanoflower balls. The interconnected nanosheets build a conductive network to provide a channel for the migration of electrons. Then, nanoflower ball NiS is prepared by high temperature sulfurization method. x / MoS 2Composite materials. During the sulfurization process, accompanied by heterogeneous formation and drastic movement of surface charges, multiple heterogeneous interfaces and sulfur vacancies and other defects induce a strong polarization effect, which significantly improves the polarization loss capacity of the material; controlling the sulfurization concentration to achieve NiS, MoS 2 Two-phase coexistence or NiS, NiS 2 、MoS 2 The coexistence of three phases enriches the heterogeneous interface and enhances the interface polarization effect; and the three-dimensional nanoflower spherical structure optimizes the impedance matching of the composite material, which is beneficial to multiple reflections and scattering of electromagnetic waves, further improving the absorption efficiency.

[0029] NiS x / MoS 2 The composite material is prepared by self-assembly of nickel-molybdenum precursor nanosheets prepared from molybdenum source and nickel source to form 3D nano flower balls, and the 3D nano flower balls are prepared by sulfurization reaction with a sulfur source; wherein NiS x NiS or NiS 2 ,NiS x / MoS 2 The composite material is NiS / MoS 2 Composite material or NiS / NiS 2 / MoS 2 Composite materials.

[0030] In some specific embodiments, when the amount of sulfur source added is 1 to 6.5 mmol, NiS x / MoS 2 The composite material is composed of NiS and MoS 2 When the sulfur source addition amount is 6.5~18mmol, NiS x / MoS 2 The composite material is composed of NiS, NiS 2 and MoS 2 .

[0031] In some embodiments, the 3D nanoflower ball is self-assembled from nanosheets with smooth surfaces and clear edges to present a uniform flower ball-like microstructure; NiS x / MoS 2 The composite material retains the structure of 3D nanoflower balls, and the nanosheets are curled due to the vulcanization reaction.

[0032] NiS x / MoS 2 The preparation method of the composite material specifically comprises the following steps:

[0033] S1. Dissolve the molybdenum source, nickel source and hexamethylenetetramine in water and stir thoroughly to obtain a uniform solution;

[0034] S2, the solution prepared in step S1 is subjected to a hydrothermal reaction, after the reaction is completed, it is cooled to room temperature, the precipitate is taken out, washed, and dried to obtain a Ni-Mo precursor;

[0035] S3, annealing the Ni-Mo precursor and the sulfur source under a specific atmosphere to obtain nano-flower-shaped NiS x / MoS 2 Composite materials.

[0036] In some specific embodiments, the molybdenum source is (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, the nickel source is Ni(NO 3 ) 2 6H 2 O, the sulfur source is thiourea, and the water is deionized water.

[0037] In some specific embodiments, in step S1 (NH 4 ) 6 Mo 7 O 24 ·4H 2 O dosage is 1~3mmol, Ni(NO 3 ) 2 6H 2 The amount of O used is 5-20 mmol, the amount of hexamethylenetetramine used is 15-25 mmol, the amount of deionized water used is 80-90 ml, and the stirring time is 5-30 min.

[0038] In some specific embodiments, the hydrothermal reaction temperature in step S2 is 100-250°C, the reaction time is 10-20h, the heating rate and the cooling rate are 1-5°C / min; deionized water and ethanol are used for centrifugal washing in step S2 to a pH of 6-7; the drying treatment in step S2 is: drying at 70-90°C overnight.

[0039] In some specific embodiments, the annealing temperature in step S3 is 350-500° C., and the annealing time is 2-4 hours.

[0040] In some specific embodiments, the specific atmosphere in S3 is Ar atmosphere.

[0041] The above NiS x / MoS 2 Composite material or NiS x / MoS 2 Preparation method of composite material NiS x / MoS 2 Composite materials are used in the field of electromagnetic microwave absorption.

[0042] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0043] Embodiment 1:

[0044] NiS / MoS 2 The composite material is prepared by self-assembly of nickel-molybdenum precursor nanosheets to form 3D nano flower balls, and the 3D nano flower balls are reacted with thiourea through a sulfurization reaction.

[0045] NiS / MoS 2 The preparation method of the composite material specifically comprises the following steps:

[0046] S1, 1.43mmol (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, 10mmol Ni(NO 3 ) 2 6H 2 O and 20 mmol hexamethylenetetramine were dissolved in 80 mL of deionized water and stirred until they were fully dissolved to obtain a uniform solution;

[0047] S2, transferring the mixed solution prepared in step S1 to a 100 mL stainless steel autoclave for hydrothermal reaction, heating to 150° C. and keeping the temperature for 12 h, cooling to room temperature (heating rate and cooling rate are both 3° C. / min), taking out the precipitate, washing it three times with deionized water and ethanol by centrifugation until the pH is 6-7, and drying it at 80° C. overnight to finally obtain a Ni-Mo precursor;

[0048] S3, the Ni-Mo precursor prepared in step S2 was placed downstream of the tube furnace, 200 mg of thiourea was placed upstream, and annealed at 400 °C in an Ar atmosphere for 2 h to obtain nano-flower spherical NiS / MoS 2 Composite materials.

[0049] like Figure 1 (a) and Figure 1 As shown in (c), the Ni-Mo precursor is a nanoflower-like structure, NiS / MoS 2 The composite material maintains the nanoflower-like structure, but due to the sulfurization treatment, NiS / MoS 2 The nanosheets of the composite material show a certain degree of curling, and the degree of curling changes with the change of sulfurization concentration.

[0050] like Figure 4 As shown in (a), when 200 mg of thiourea was added for sulfurization reaction, nanoflower-shaped NiS / MoS 2The composite material has a minimum reflection loss of -14dB and a maximum effective absorption bandwidth of 2.2GHz.

[0051] Embodiment 2:

[0052] NiS / MoS 2 The composite material is prepared by self-assembly of nickel-molybdenum precursor nanosheets to form 3D nano flower balls, and the 3D nano flower balls are reacted with thiourea through a sulfurization reaction.

[0053] NiS / MoS 2 The preparation method of the composite material specifically comprises the following steps:

[0054] S1, 1.43mmol (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, 10mmol Ni(NO 3 ) 2 6H 2 O and 25 mmol hexamethylenetetramine were dissolved in 90 mL of deionized water and stirred until they were fully dissolved to obtain a uniform solution;

[0055] S2, transferring the mixed solution prepared in step S1 to a 100 mL stainless steel autoclave for hydrothermal reaction, heating to 200° C. and keeping the temperature for 12 h, cooling to room temperature (heating rate and cooling rate are both 5° C. / min), taking out the precipitate, washing it three times with deionized water and ethanol by centrifugation until the pH is 6-7, and drying it at 80° C. overnight to finally obtain a Ni-Mo precursor;

[0056] S3, the Ni-Mo precursor prepared in step S2 was placed downstream of the tube furnace, 400 mg of thiourea was placed upstream, and annealed at 400 ° C in Ar atmosphere for 2 h to obtain nano-flower spherical NiS / MoS 2 Composite materials.

[0057] like Figure 4 As shown in (b), when 400 mg of thiourea was added for sulfurization reaction, nanoflower-shaped NiS / MoS 2 The composite material has a minimum reflection loss of -31dB and a maximum effective absorption bandwidth of 5.6GHz.

[0058] Embodiment 3:

[0059] NiS / NiS 2 / MoS 2 The composite material is prepared by self-assembly of nickel-molybdenum precursor nanosheets to form 3D nano flower balls, and the 3D nano flower balls are reacted with thiourea through a sulfurization reaction.

[0060] NiS / NiS 2 / MoS 2 The preparation method of the composite material specifically comprises the following steps:

[0061] S1, 2.15mmol (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, 15mmol Ni(NO 3 ) 2 6H 2 O and 25 mmol hexamethylenetetramine were dissolved in 90 mL of deionized water and stirred until they were fully dissolved to obtain a uniform solution;

[0062] S2, transferring the mixed solution prepared in step S1 to a 100 mL stainless steel autoclave for hydrothermal reaction, heating to 200° C. and keeping the temperature for 12 h, cooling to room temperature (heating rate and cooling rate are both 5° C. / min), taking out the precipitate, washing it three times with deionized water and ethanol by centrifugation until the pH is 6-7, and drying it at 80° C. overnight to finally obtain a Ni-Mo precursor;

[0063] S3, the Ni-Mo precursor prepared in step S2 was placed downstream of the tube furnace, 600 mg of thiourea was placed upstream, and annealed at 400 °C in an Ar atmosphere for 2 h to obtain nano-flower spherical NiS / NiS 2 / MoS 2 Composite materials.

[0064] like Figure 2 As shown in Figure (a), clear nanosheets can be observed on the surface of the nanoflower ball; Figure (b) clearly shows the NiS and NiS 2 and MoS 2 The three phases coexist, with lattice spacings of 0.62 nm, 0.22 nm, and 0.28 nm corresponding to MoS 2 The (002) crystal plane of NiS, the (211) crystal plane of NiS 2 (200) crystal plane; a large number of discontinuous lattice fringes, vacancies and defects can be observed in Figures (c) and (d). 2 and MoS 2 The generation of atomic-level dislocations and defects at the heterojunction interfaces of phase formation.

[0065] like Figure 4 As shown in (c), when 600 mg of thiourea was added for sulfurization reaction, nano-flower-shaped NiS / NiS 2 / MoS 2 Composite materials, NiS, NiS 2and MoS 2 The three phases coexist with a minimum reflection loss of -71.3dB and a maximum effective absorption bandwidth of 6GHz.

[0066] Embodiment 4:

[0067] NiS / NiS 2 / MoS 2 The composite material is prepared by self-assembly of nickel-molybdenum precursor nanosheets to form 3D nano flower balls, and the 3D nano flower balls are reacted with thiourea through a sulfurization reaction.

[0068] NiS / NiS 2 / MoS 2 The preparation method of the composite material specifically comprises the following steps:

[0069] S1, 1.43mmol (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, 10mmol Ni(NO 3 ) 2 6H 2 O and 20 mmol hexamethylenetetramine were dissolved in 80 mL of deionized water and stirred until they were fully dissolved to obtain a uniform solution;

[0070] S2, transferring the mixed solution prepared in step S1 to a 100 mL stainless steel autoclave for hydrothermal reaction, heating to 150° C. and keeping the temperature for 12 h, cooling to room temperature (heating rate and cooling rate are both 3° C. / min), taking out the precipitate, washing it three times with deionized water and ethanol by centrifugation until the pH is 6-7, and drying it at 90° C. overnight to finally obtain a Ni-Mo precursor;

[0071] S3, the Ni-Mo precursor prepared in step S2 was placed downstream of the tube furnace, 1000 mg of thiourea was placed upstream, and annealed at 450 ° C for 3 h in an Ar atmosphere to obtain nano-flower spherical NiS / NiS 2 / MoS 2 Composite materials.

[0072] like Figure 4 As shown in (d), when 1000 mg of thiourea was added for sulfurization reaction, nano-flower-shaped NiS / NiS 2 / MoS 2 Composite materials, NiS, NiS 2 and MoS 2 The three phases coexist with a minimum reflection loss of -26.7dB and a maximum effective absorption bandwidth of 4.6GHz.

[0073] Embodiment 5:

[0074] NiS / MoS prepared in any one of Examples 1-2 2 Composite material or NiS / NiS prepared in any one of Examples 3-4 2 / MoS 2 Composite materials are used in the field of electromagnetic wave absorption technology.

[0075] Comparative Example 1:

[0076] The difference from Example 1 is that the Ni-Mo precursor is not subjected to sulfurization treatment, specifically:

[0077] S3, the Ni-Mo precursor was placed in air and annealed at 400 °C for 2 h to prepare nano-flower spherical NiMoO 4 Material.

[0078] Comparative Example 2:

[0079] The difference from Example 3 is that the Ni-Mo precursor is not subjected to sulfurization treatment, specifically:

[0080] S3, the Ni-Mo precursor was placed in air and annealed at 400 °C for 2 h to prepare nano-flower spherical NiMoO 4 Material.

[0081] Reference Figure 1 (b) NiMoO prepared in Comparative Example 1 and Comparative Example 2 4 The materials are all nano flower ball structures, combined with Figure 3 (a) Figure 3 (b) It can be seen that the nanoflower-shaped NiS / NiS obtained after sulfidation sublimation treatment 2 / MoS 2 The composite material has a smaller minimum reflection loss and a larger effective absorption bandwidth, indicating that the performance of the composite material prepared by vulcanization treatment is better.

[0082] Depend on Figure 4 It can be seen that with the increase of sulfurization concentration (increase of thiourea addition), the formation of heterogeneous interfaces leads to an increase in sulfur vacancies. The use of sulfur vacancies as electron traps further improves electron transport and dipole polarization, which is beneficial to the improvement of the conductivity of the composite material and the enhancement of conduction loss and polarization loss, and obtains stronger EMW absorption performance. However, when the degree of sulfurization is too high (too much thiourea is added), the sulfur vacancy concentration will decrease after reaching saturation, thus resulting in Figure 4 (d) NiS / NiS 2 / MoS 2 The absorption properties of composite materials are not ideal.

[0083] Figure 5(a) is NiS prepared in Examples 1-4 of the present invention. x / MoS 2 Three-dimensional graph of minimum reflection loss of composite materials corresponding to minimum reflection loss at different thicknesses, NiS / NiS prepared in Example 3 2 / MoS 2 Composite materials have minimal reflection losses.

[0084] In summary, compared with the prior art, the present invention has the following beneficial effects:

[0085] 1. The present invention first synthesizes Ni-Mo precursor material by hydrothermal method. During the synthesis of Ni-Mo precursor, two-dimensional nanosheets self-assemble to form 3D nano flower balls. The interconnected nanosheets construct a conductive network to provide a channel for the migration of electrons. Then, nano flower ball NiS is prepared by high temperature sulfurization method. x / MoS 2 During the sulfurization process, accompanied by heterogeneous formation and drastic movement of surface charges, multiple heterogeneous interfaces and sulfur vacancies and other defects induce a strong polarization effect, which significantly improves the NiS x / MoS 2 Polarization loss capability of composite materials;

[0086] 2. In the present invention, NiS and MoS 2 Two-phase coexistence or NiS, NiS 2 and MoS 2 The coexistence of three phases, especially the coexistence of three phases, is conducive to enriching the heterogeneous interface and enhancing the interface polarization effect; and the three-dimensional nanoflower spherical structure optimizes the NiS x / MoS 2 The impedance matching of composite materials, when applied in the field of electromagnetic wave absorption, is beneficial to multiple reflections and scattering of electromagnetic waves, further improving the electromagnetic wave absorption efficiency.

[0087] 3. The present invention controls the amount of sulfur source (i.e., thiourea) added during the sulfurization reaction to control the sulfurization concentration. When the sulfurization concentration is high, NiS and NiS 2 and MoS 2 Three-phase composite materials, but the sulfurization concentration should not be too high, otherwise the performance of the three-phase composite materials will decrease; when the sulfurization concentration is low, NiS and MoS 2 Two-phase composite materials, but the vulcanization concentration should not be too low, otherwise the performance of the formed two-phase composite materials will also decrease.

[0088] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0089] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A NiS x / MoS2 composite material, characterized in that The 3D nano flower balls are formed by self-assembly of Ni-Mo precursor nanosheets prepared from molybdenum source and nickel source, and the 3D nano flower balls are prepared by sulfurization reaction with a sulfur source; wherein NiS x NiS or NiS2, the NiS x / MoS2 composite material is NiS / MoS2 composite material or NiS / NiS2 / MoS2 composite material.

2. NiS according to claim 1 x / MoS2 composite material, characterized in that When the amount of sulfur source added is 1 to 6.5 mmol, the NiS x / MoS2 composite material is composed of NiS and MoS2; when the sulfur source is added in an amount of 6.5 to 18 mmol, the NiS x The components of the / MoS2 composite material are NiS, NiS2 and MoS2.

3. NiS according to claim 1 x / MoS2 composite material, characterized in that The 3D nano flower ball is self-assembled by nanosheets with smooth surface and clear edges to present a uniform flower ball-like microstructure; the NiS x The MoS2 / MoS2 composite material retains the structure of the 3D nanoflower balls, and the nanosheets are curled due to the sulfurization reaction. 4.NiS x A method for preparing a / MoS2 composite material, characterized in that: The specific steps include: S1. Dissolve the molybdenum source, nickel source and hexamethylenetetramine in water and stir thoroughly to obtain a uniform solution; S2, the solution prepared in step S1 is subjected to a hydrothermal reaction, after the reaction is completed, it is cooled to room temperature, the precipitate is taken out, washed, and dried to obtain a Ni-Mo precursor; S3, annealing the Ni-Mo precursor and the sulfur source under a specific atmosphere to obtain nano-flower-shaped NiS x / MoS2 composite materials.

5. NiS according to claim 4 x A method for preparing a / MoS2 composite material, characterized in that: The molybdenum source is (NH4)6Mo7O 24 ·4H2O, the nickel source is Ni(NO3)2·6H2O, the sulfur source is thiourea, and the water is deionized water.

6. NiS according to claim 5 x A method for preparing a / MoS2 composite material, characterized in that: In step S1, (NH4)6Mo7O 24 The amount of 4H2O used is 1-3 mmol, the amount of Ni(NO3)2·6H2O used is 5-20 mmol, the amount of hexamethylenetetramine used is 15-25 mmol, the amount of deionized water used is 80-90 ml, and the stirring time is 5-30 min.

7. NiS according to claim 4 x A method for preparing a / MoS2 composite material, characterized in that: In the step S2, the hydrothermal reaction temperature is 100-250°C, the reaction time is 10-20h, and the heating rate and cooling rate are 1-5°C / min; in the step S2, deionized water and ethanol are used for centrifugal washing until the pH is 6-7; and the drying treatment in the step S2 is: drying at 70-90°C overnight.

8. NiS according to claim 4 x A method for preparing a / MoS2 composite material, characterized in that: In step S3, the annealing temperature is 350-500° C., and the annealing time is 2-4 hours.

9. NiS according to claim 4 x A method for preparing a / MoS2 composite material, characterized in that: The specific atmosphere in S3 is Ar atmosphere.

10. NiS according to any one of claims 1 to 2 x / MoS2 composite material or NiS as described in claims 3-9 x Preparation method of NiS / MoS2 composite material x / MoS2 composite materials are used in the field of electromagnetic microwave absorption.

Citation Information

Cited By

  • MXene-based electromagnetic wave absorbing material and preparation method thereof

    CN120230512A

  • An MXene-based electromagnetic wave absorbing material and its preparation method

    CN120230512B